Pengembangan Model Pembelajaran Tematik Anak Usia Dini Berbasis Kurikulum Merdeka melalui LMS Interaktif - Ica Purnamasari; Rosyi Damayani Twinsari Maningtyas; Zihan Novita Sari (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to develop a thematic learning model for early childhood that is integrated with the Independent Curriculum and supported by an interactive Learning Management System (LMS) platform. The background of this research is the need for an adaptive, fun, and technology-based learning approach in supporting early childhood learning characteristics. The method used is a Research and Development (R&D) approach with the ADDIE development model, which includes the stages of Analysis, Design, Development, and Implementation. At the analysis stage, a study of teacher needs and children's learning characteristics was carried out through observation, interviews, and document studies. The design stage includes designing learning models, theme structures, LMS interactive features, and play-based assessment strategies. The development stage produces an interactive thematic LMS prototype that contains learning videos, digital activities, and child development reporting. The initial implementation was carried out on a limited basis in several partner PAUDs to see the response of teachers and children. The results of the study show that this model is able to increase children's involvement in learning activities, facilitate contextual and fun learning, and make it easier for teachers to plan and monitor children's learning development. This model is expected to be an innovative solution in the implementation of the Independent Curriculum in technology-based early childhood education.